Analisis Disiplin dan Inisiatif Terhadap Kinerja Pegawai Dinas Perindustrian, Perdagangan, Energi dan Sumber Daya Mineral Provinsi Sumatera Utara (Studi Kasus Perdagangan Dalam Negeri) - Putri Apriyani br Rangkuti; Wahyu Syarvina (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The success of an organization in achieving its goals depends on the quality of its employees. The main problem in human resource management which is an important point in organizations is related to employee performance issues. This research aims to analyze the influence of discipline and initiative on the performance of employees in the Domestic Trade Sector at the Department of Industry, Trade, Energy and Mineral Resources of North Sumatra Province. This research uses a descriptive analysis model with the data obtained as testing material. In this research, data collection methods are needed to answer all the research problems posed. The research results show that employee work discipline has not been implemented optimally. Some employees still do not show a high work ethic and lack discipline. However, employees already have good initiative in carrying out their duties.